(untitled) (Jurnal EurekaMatika, 2018)
Poverty is such a complex problem. Bandung Regency takes the fourth place as an area with biggest poverty population in West Java. Poverty in Bandung Regency has increased since 2014 until 2015. Hence, the goverment needs a precise implementable aid program to help Bandung Regency to handle this problem. Therefore, writer will classify some subdistricts in Bandung Regency based on poverty indicator in 2015 as variable in order to form the cluster that have similar characteristics between each components, so for each cluster that formed will have a specific criteria. Classification process will be done by Latent Class Cluster Analysis (LCCA) method. This method use EM Algorithm and Newton Raphson Method as parameter estimation process. After that, the model will be choosen based on the lowest BIC value and the classification of object into the cluster which will be done by using posterior probability. The conclusion from the results of classification process is four cluster has been obtained with the first cluster consist of 11 subdistricts, second cluster consist of 10 subdistricts, third cluster consist of 8 subdistricts, and fourth cluster consist of 2 subdistricts and each cluster has specific criteria. ABSTRAK Kemiskinan merupakan hal yang sangat kompleks. Kabupaten Bandung merupakan wilayah yang memiliki jumlah penduduk miskin keempat terbanyak di Jawa Barat. Kemiskinan di Kabupaten Bandung mengalami peningkatan dari tahun 2014 ke tahun 2015. Untuk itu diperlukan ketepatan program bantuan dari pemerintah yang bisa diterapkan di Kabupaten Bandung untuk menangani masalah tersebut. Oleh karena itu, penulis akan melakukan pengelompokan kecamatan di Kabupaten Bandung berdasarkan variabel indikator kemiskinan tahun 2015 untuk mendapatkan kelompok-kelompok (klaster) yang memiliki kemiripan sifat antara anggotanya, sehingga untuk masing-masing klaster yang terbentuk memiliki kriteria tertentu. Pengelompokan akan dilakukan dengan metode Latent Class Cluster Analysis (LCCA). Metode ini menggunakan Algoritma EM dan Metode Newton Raphson sebagai tahapan estimasi parameter. Selanjutnya pemilihan model dilakukan berdasarkan nilai BIC terendah dan pengelompokan objek ke dalam klaster dilakukan menggunakan peluang posterior. Kesimpulan dari hasil pengelompokan ini adalah terbentuknya 4 klaster dengan klaster 1 terdiri dari 11 kecamatan, klaster 2 terdiri dari 10 kecamatan, klaster 3 terdiri dari 8 kecamatan dan klaster 4 terdiri dari 2 kecamatan dengan masing-masing klaster memiliki kriteria tertentu.s